Identification of Electrical Circuit Material Science Misconceptions in Class VI SD UMP Students - Rifqi Maulana; Subuh Anggoro; Ristiana Dyah Purwandari (UM Purwokerto Press, 2023)
A misconception is a wrong belief in a concept, idea, object, or event that is inconsistent with the scientific understanding accepted by experts in that field. The problem studied in this study is the impact of misconceptions that occur in the material for electrical circuits among UMP Elementary School students. This type of research is descriptive with a quantitative approach that is carried out in a definite way to help misconceive the material for electrical circuits using essay questions for SD UMP students. The data obtained in this study included the participation of sixth grade students at SD UMP in answering essay questions, the results of interviews with teachers, and documentation. The data analysis used is quantitative descriptive analysis. The results of the study showed that there were 11.33% misconceptions about electrical circuits in UMP Elementary School students, namely, 11.33% did not understand the concept of electrical circuits, 48% had misconceptions, and 40.67% understood concepts. Misconceptions with high categories that occur in the problem indicators determine how to read electrical circuits in illustrated images, namely 29%.